Implementation of the Problem Posing Model in Islamic Religious Education Learning - Murharyana, Murharyana; Al Ayyubi, Ibnu Imam; Hayati, Ai Faridatul; Nurfajriyah, Dewi Syifa; Ikromi, Shoutika Nawadya (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This research analyzes student learning outcomes in Islamic Religious Education based on student gender. This research used a quantitative approach which was carried out at SMPN 1 Wanayasa, SMPN 2 Parongpong, and SMP Unggulan Al Amin. The method in this research uses the survey method and Analysis of Variance test with a population of 1013 sample students with 31 students at SMPN 1 Wanayasa, 32 students at SMPN 2 Parongpong, and 32 students at SMP Unggulan Al Amin with a total of 95 students based on purposive techniques example. This research instrument uses tests that have been tested for validity, reliability, difficulty index, and distinguishing power by testing the data analysis requirements consisting of normality tests using Kolmogorov-Smirnov and Shapiro-Wilk. In this research, it can be concluded that there are differences in the learning outcomes of students in Islamic Religious Education whose learning uses the problem logging model and the interaction between the problem position model which is viewed based on the gender of the students. Still, between male and female students there is no significant difference or can is said to tend to be the same in Islamic Religious Education learning. This is proven by the significance values ​​for the data variables school, gender, and school*gender of 0.000, 0.062, and 0.008.